Potential Water Saving through System of Rice Intensification (SRI) in Terai Region of West Bengal, India - Mitra, Biplab; Mookherjee, Saikat; Biswas, Sujan; Mukhopadhyay, Prabir (International Journal of Bio-resource and Stress Management, 2013)
On farm demonstrations were conducted during three consecutive years (Summer, 2009, 2010 and 2011) in farmer’s field of four adopted villages of Cooch Behar Krishi Vigyan Kendra to assess the potential water saving in boro rice through SRI. A total of 40 demonstrations were conducted covering an area of 85.6 ha. In each year, 12-15 innovative and receptive farmers were selected from the villages for conducting the trials ensuring their active participation. Experimental results indicated the superiority of SRI (72.64 q ha-1) over conventional method (54 q ha-1) in boro season. The yield increment in SRI was recorded to be 34.51% over the conventional method. The water application was significantly higher in conventional method (15200 m3) as compared to SRI method (12100 m3) as measured through water meter. Water productivity indicated the lower values in conventional system (0.36 kg grain m-3) as compared to SRI (0.60 kg grain m-3) signifying higher grain yield with application of lesser irrigation water under SRI. The SRI method also registered higher net income (`Rs. 41204 ha-1) and benefit-cost ratio (2.11) against the conventional practice of rice cultivation. Moreover, there was a saving of 20.39% irrigation water besides achieving higher grain yield.